Multifragmentary patellar fracture has a distinct fracture pattern which makes coronal split, inferior pole, or satellite fragments - Jae-Woo Cho (Nature Portfolio, 2021)
Abstract The present study aimed to map the location and frequency of fracture lines on the coronal articular and sagittal planes in multifragmentary patellar fractures. 66 multifragmentary patellar fractures were digitally reconstructed using the 3D CT mapping technique. The coronal articular surface and midsagittal fracture maps were produced by superimposing each case over a single template. Each fracture line was classified based on the initial displacement and orientation. We evaluated the frequency and direction of the fracture line, coronal split fragment area, and satellite and inferior pole fragment presence. Coronal articular surface fracture mapping identified primary horizontal fracture lines between the middle and inferior one-third of the articular surface in 63 patients (95.4%). Secondary horizontal fracture lines running on the inferior border of the articular facet were confirmed (83.3%). Secondary vertical fracture lines creating satellite fragments were mostly located on the periphery of the bilateral facet. Midsagittal fracture mapping of primary and secondary horizontal fracture lines with the main coronal fracture line revealed a predominantly X-shaped fracture map. The consequent coronal split fragment and inferior pole fracture were combined in most cases. In conclusion, the multifragmentary patellar fracture has a distinct pattern which makes coronal split, inferior pole, or satellite fragments.